THE ROLE OF COMPETENCE-BASED LESSON PLANNING IN DEVELOPING COMMUNICATIVE SKILLS AMONG HIGH SCHOOL STUDENTS - Shahnoza Ochildiyeva (International Journal of Literature and Language Studies, 2026)
This article explains the role of effective lesson planning in improving communicative competence among high school students. Language is considered an interconnected system in which all components should be developed in order to improve overall language proficiency. This research briefly introduces the four communicative competences and presents fruitful methods and activities that can be used during lessons. Moreover, it discusses how to organize lessons based on competences while keeping students engaged throughout the learning process. The article also highlights the importance of Communicative Language Teaching (CLT) and effective lesson planning in achieving successful learning outcomes.